Pengaruh Model Pembelajaran Demonstrasi terhadap Hasil Belajar IPA Siswa Kelas 4 pada Materi Bagian dan Fungsi Bunga Sempurna di UPTD SDN 010090 Kisaran Kota - Sri Darma Asmaniyah; Nur Wahyuni; Muhammad Dekar (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of the demonstration learning model on the science learning outcomes of fourth-grade students on the topic of the parts and functions of a complete flower at UPTD SDN 010090 Kisaran Kota. The demonstration learning model was chosen because it is believed to improve students’ understanding through concrete and interactive learning experiences.The research method used was a quasi-experimental design with a pretest-posttest control group design. The sample consisted of two classes: an experimental class that applied the demonstration learning model and a control class that used conventional teaching methods. The sampling technique employed was purposive sampling. Data were collected through learning outcome tests administered before and after the treatment.Data analysis was conducted using a t-test to determine whether there was a significant difference between the two groups. The results showed a significant difference in learning outcomes between students taught using the demonstration learning model and those taught using conventional methods. The average learning outcomes of students in the experimental class were higher than those in the control class.This indicates that the use of the demonstration learning model has a positive effect on students’ science learning outcomes, particularly on the topic of the parts and functions of a complete flower. Therefore, the demonstration learning model can be an effective alternative teaching strategy to enhance students’ understanding of science concepts, especially for materials that require visualization and hands-on practice.